Use Of Cosmetics In Pregnant Women During Pregnancy - Neti Sulami; Nini Niatullah Aliyati; Elfiana Fitri; Defi, Defi (Jurnal EduHealth, 2024)
Cosmetic products are a daily necessity and are widely used by young women, including pregnant women. Recent cross-sectional studies show 60–80% of pregnant women also use cosmetic products, including facial cleanser, day cream, foundation, mascara, lipstick, eye pencil, eye shadow and makeup remover. Cosmetic products contain various chemical substances (e.g. phthalates, parabens, formaldehyde, dioxane, nitrosamines, hydroquinone, phenols, organic solvents) and heavy metals (e.g. Pb, Hg, As, Cd, Cr, Sb, Ni), which are added intentionally. as an efficacy component to increase the skin care effect of cosmetic products or brought from raw materials, auxiliary materials or technical problems during the production process. The aim of this research is to determine the use of cosmetics by pregnant women during pregnancy. The research target is pregnant women in Bima City. The sampling technique is purposive sampling and data analysis by calculating the frequency distribution. The result showing Based on the data above, it shows that the majority of pregnant women use whitening during pregnancy, namely 30%, the duration of use of cosmetics in most pregnant women is >1 year, namely 30%, the majority of pregnant women use cosmetics during pregnancy because it becomes a need/habit, namely 40%, the effects arising from the use of cosmetics during pregnancy during pregnancy mostly have a brightening effect of 33.33%, and the knowledge of pregnant women is in the good category, namely 83.33%.